The Concept of Halal Tourism: Between Business or Islamication Process? - Khairul Anwar (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
Halal tourism is one type of new tourism concept that has adhered to the principle of regularity guided by Islamic teachings. The purpose of this study is to describe the concept of halal tourism. Because the concept of halal tourism which has been proclaimed by the government, is misunderstood by the public. Misguided in understanding the concept of halal tourism in the community certainly raises pros and cons. This type of research belongs to the genre of literature writing, which involves obtaining data and information from library sources such as books, research results, journals, and other reading materials that are still relevant to the research problem. The research findings explain that the concept of halal tourism means the fulfillment of halal service facilities that are friendly for Muslim tourists and in tourist destinations such as restaurant accommodation or halal food. Then there are adequate places of worship and other halal tourism facilities. In essence, the concept of halal tourism emphasizes more on sharia services, not meaning the process of Islamization or crashing into local wisdom